2016
DOI: 10.1155/2016/9096549
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol Preconditioning: An Effective Strategy to Prevent Liver Ischemia Reperfusion Injury

Abstract: Hepatic ischemia reperfusion injury (IRI) is an inevitable clinical problem for liver surgery. Polyethylene glycols (PEGs) are water soluble nontoxic polymers that have proven their effectiveness in various in vivo and in vitro models of tissue injury. The present study aims to investigate whether the intravenous administration of a high molecular weight PEG of 35 kDa (PEG 35) could be an effective strategy for rat liver preconditioning against IRI. PEG 35 was intravenously administered at 2 and 10 mg/kg to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
(50 reference statements)
2
21
0
Order By: Relevance
“…(40) It has been described that the activation of both AKT and AMPK is part of a protective mechanism to prevent IRI. (41) Our results agree with this notion, showing increases not only in the pAKT/AKT ratio but also in the pAMPK to AMPK ratio in hCOX-2-Tg mice after IRI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(40) It has been described that the activation of both AKT and AMPK is part of a protective mechanism to prevent IRI. (41) Our results agree with this notion, showing increases not only in the pAKT/AKT ratio but also in the pAMPK to AMPK ratio in hCOX-2-Tg mice after IRI.…”
Section: Discussionsupporting
confidence: 91%
“…The increase in the pAKT/AKT ratio in hCOX‐2‐Tg mice after IRI may be due to a direct AKT activation through COX‐2‐dependent PGE 2 acting through EP2/EP4 Gβγ dimers, as reported by Rizzo . It has been described that the activation of both AKT and AMPK is part of a protective mechanism to prevent IRI . Our results agree with this notion, showing increases not only in the pAKT/AKT ratio but also in the pAMPK to AMPK ratio in hCOX‐2‐Tg mice after IRI.…”
Section: Discussionsupporting
confidence: 91%
“…More recently, it has been demonstrated that intravenous (i.v.) PEG35 administration is also protective against liver warm ischemia reperfusion injury [ 25 ]. This protection has been reviewed in other organs, such as pancreas in an inflammation model [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the wide diversity of mechanisms involved in IRI, many therapeutic mechanisms have been suggested to prevent hepatic damage [ 7 ]. Pharmacological interventions [ 2 , 8 , 9 , 10 ] and the different preconditioning mechanisms are the most common strategies [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%